2008
DOI: 10.1007/978-3-540-68566-1_1
|View full text |Cite
|
Sign up to set email alerts
|

A Study on how Humans Describe Relative Positions of Image Objects

Abstract: Information describing the layout of objects in space is commonly conveyed through the use of linguistic terms denoting spatial relations that hold between the objects. Though progress has been made in the understanding and modelling of many individual relations, a better understanding of how human subjects use spatial relations together in natural language to is required. This paper outlines the design and completion of an experiment resulting in the collection of 1920 spoken descriptions from 32 human subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…A classificação dos termos de relações espaciais foi realizada a partir das classes: topológica, direcional e de distância, já existentes em estudos sobre relações espaciais (Bruns & Egenhofer, 1998;Shariff et al, 1998;Wang et al, 2008;Coventry, 2013). A classificação dos termos de relação espacial encontrados colaborará com aplicações computacionais na distinção dos termos que podem ser utilizados para cada classe.…”
Section: Discussionunclassified
“…A classificação dos termos de relações espaciais foi realizada a partir das classes: topológica, direcional e de distância, já existentes em estudos sobre relações espaciais (Bruns & Egenhofer, 1998;Shariff et al, 1998;Wang et al, 2008;Coventry, 2013). A classificação dos termos de relação espacial encontrados colaborará com aplicações computacionais na distinção dos termos que podem ser utilizados para cada classe.…”
Section: Discussionunclassified
“…Two objects are randomly selected from the pool, randomly resized, rotated and placed in a digital image. The procedure, which is similar as that followed by Wang et al in [9], is repeated 800 times. 800 synthetic images are therefore created.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies on how people describe images can be found in the literature [Jörgensen, 1998;Laine-Hernandez and Westman, 2006;Greisdorf and O'Connor, 2002;Wang et al, 2008]. The main objective of most of these studies is analysing people's image descriptions for image retrieval in databases.…”
Section: Outlining the Model For Qualitative Image Description (Qid)mentioning
confidence: 99%
“…Research by Wang et al [2008] on how humans describe relative positions of image objects show that the relations of direction (right, left, above, below ), topology (overlap, separate, touch, in, out, etc.) and distance (far, near, etc.)…”
Section: Outlining the Model For Qualitative Image Description (Qid)mentioning
confidence: 99%